CHARACTERISTICS OF HUMAN RESOURCE PLANNING IN HEALTHCARE - Tsvetelina Mihaylova; Tsvetomir Dimitrov; Neli Gradinarova; Desislava Todorova (Peytchinski Publishing, 2018)
The planning may be determined as prediction and prognosis making of human resources in a long-term plan, in conformity with the aims of the particular healthcare institution. It is prepared by the medical manager based on different analyses and prognoses with the purpose of ensuring the needed number of human resources. The aim of the study is an exploration of some of the reasons for the shortage of human resources in the healthcare system. In order to be achieved the realization of the aim set, a task was assigned for analysis of the main aspects of human resource planning in the healthcare system. Data from available scientific sources on the subject were used; they were published in different scientific issues. The results from the study demonstrate that the human resource planning is usually determined by the volume of work, however, due to the specificity of the activities in the health care system, it is usually determined by the type of labour functions - basic, governing, assisting. The future needs of personnel are fully determined by the mission, strategy, and aims of the organization. A conclusion may be drawn that the human resource planning is a necessary condition for effective management of human resources, and it has a significant and decisive role in the prosperity of the particular hospital.